1997
DOI: 10.1080/09500349708231878
|View full text |Cite
|
Sign up to set email alerts
|

Quantum correlations, local interactions and error correction

Abstract: We consider the effects of local interactions upon quantum mechanically entangled systems. In particular we demonstrate that non-local correla-PACS number(s) 03.65

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
(23 reference statements)
0
19
0
Order By: Relevance
“…Note also that the classical communication from Alice to Bob in step 2 above is crucial because otherwise the protocol would be impossible to execute (there is a deeper reason for this: if we could perform teleportation without classical communication then Alice could send messages to Bob faster than the speed of light, see e.g. Vedral et al (1997c)). …”
Section: B Teleportationmentioning
confidence: 99%
“…Note also that the classical communication from Alice to Bob in step 2 above is crucial because otherwise the protocol would be impossible to execute (there is a deeper reason for this: if we could perform teleportation without classical communication then Alice could send messages to Bob faster than the speed of light, see e.g. Vedral et al (1997c)). …”
Section: B Teleportationmentioning
confidence: 99%
“…Note also that the classical communication from Alice to Bob in step 2 above is crucial because otherwise the protocol would be impossible to execute (there is a deeper reason for this: if we could perform teleportation without classical communication then Alice could send messages to Bob faster than the speed of light, see e.g. [38]).…”
Section: A a Basic Description Of Teleportationmentioning
confidence: 99%
“…Although one can perform entanglement purification acting on a single pair of particles only [7,21,38], it can be shown that there are states that cannot be purified in this way [27]. Therefore we present a scheme that acts on two pairs simultaneously.…”
Section: A Entanglement Purificationmentioning
confidence: 99%
“…Now, the second stage is the occurrence of errors, represented by the operators {E i } which act on the state of the system only, after which we have i E i |ψ c |m |e i Note that at this stage the measurement has not yet been made so that the state of the apparatus is still disentangled from the rest. In general, the states of the environment |e i need not be orthogonal (Vedral et al 1997). If they are orthogonal this leads to a specific form of decoherence which we might call "dephasing" and will be analysed later.…”
Section: Quantum Error Correction As Maxwell's Demonmentioning
confidence: 99%